Endocrine Neoplasia - Sturgeon, Cord.; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Endocrine Neoplasia provides a broad overview of the neoplastic conditions of extracranial endocrine glands not involved in reproduction. Benign and malignant tumors of the thyroid, parathyroid glands, adrenals, and neuroendocrine pancreas are covered. Special emphasis is on the detection, surgical treatment, targeted non-cytotoxic adjuvant therapy, surveillance, and genetics of these tumors. Standard chemotherapy and radiation treatments are discussed. This book is pertinent to practicing oncologists, surgical oncologists, endocrinologists, endocrine surgeons, otolaryngologists, and fellows and residents of these disciplines. "Endocrine neoplasia encompasses a spectrum of benign and malignant tumors. In this text, noted experts in the field discuss the biologic characteristics and clinical management of these challenging entities. This book will be a unique resource for both physicians and scientists." - Steven T. Rosen, M.D., Series Editor
Thyroid -- The Biology of Thyroid Oncogenesis -- Evaluation of the Thyroid Nodule -- Differentiated Thyroid Cancers of Follicular Cell Origin -- Sporadic Medullary Thyroid Cancer -- Anaplastic Thyroid Cancer -- Parathyroid -- Primary Hyperparathyroidism -- Parathyromatosis and Parathyroid Cancer -- Adrenal -- Incidentaloma -- Pheochromocytoma and Paraganglioma -- Functional Cortical Neoplasms -- Adrenocortical Carcinoma -- Pancreatic Neuroendocrine Tumors -- Gastrinoma -- Insulinoma -- Rare Neuroendocrine Tumors of the Pancreas -- Multiple Endocrine Neoplasia -- The Menin Gene -- Multiple Endocrine Neoplasia Type 1: Clinical Manifestations and Management -- The RET Protooncogene -- Multiple Endocrine Neoplasia Type 2: Clinical Manifestations and Management.
Keywords: Medicine; Endocrinology; Oncology; Surgery; Medicine & Public Health; Oncology; Surgery; Endocrinology